Effects of Xeroderma pigmentosum group C polymorphism on the likelihood of prostate cancer. Issue 9 (2nd June 2020) - Yan, Yidan; Xu, Jianmin; Xu, Bin; Wen, Qiaxian; Zhou, Jing; Zhang, Lifeng; Zuo, Li; Lv, Guoqiang; Shi, Yunfeng
Abstract: Background: Numerous studies have assessed the association between xeroderma pigmentosum complementation group C (XPC) polymorphisms and susceptibility of prostate cancer (PCa); however, the findings remain inconsistent. Methods: We performed an updated analysis utilizing data from electronic databases to obtain a more accurate estimation of the relationship between XPC rs2228001 A/C polymorphism and PCa risk. We further used in silico tools to investigate this correlation. Results: Totally, 5, 305 PCa cases and 6, 499 control subjects were evaluated. When all studies pooled together, we detected no positive result (recessive genetic model: OR = 1.14, 95% CI = 0.93‐1.40, P heterogeneity = 0.001, P = .212); nevertheless, the XPC rs2228001 A/C variant was associated with PCa risk in Asian descendants in the subgroup analysis (OR = 1.21, 95% CI = 1.01‐1.43, P heterogeneity = 0.008, P = .034). In silico tools showed that more than 20 proteins can participate in the protein crosstalk with XPC. The expression of XPC was down‐regulated in all Gleason scores of prostate cancer. Conclusions: The present study indicated that the XPC rs2228001 A/C variant may be associated with elevated PCa risk in Asian patients.